Cancer-related fatigue and its association with health-related quality of - Hasanvand, Shirin; Ashktorab, Tahereh; Jafari, Zohreh; Salmani, Nayereh; Safariyan, Zeinab (Advances in Nursing & Midwifery, 2015)
Abstract Background and aim: Fatigue is one of the most common complications and symptoms of cancer. It affects on people's ability and quality of life and functional status. This study examined Cancer-related fatigue and relationship with health-related quality of life and functional status of cancer patients. Materials and Methods: In this corelational descriptive study, 57 cancer patients were selected by consecutive sampling. Fatigue, quality of life and functional status of patients measured by the Fatigue Severity Scale (FSS), FACT–G and Karnofsky Performance Scale. Validity and reliability of questionnaires were investigated by content validity and alpha chronbach. Data analysis was done by descriptive statistics and Pearson correlation coefficient, T test, Mann-Whitney, Kruskal-Wallis and ANOVA. Results: The mean fatigue score of samples was 4/36. The overall mean of QoL was 66 (14/65) and 5/89% of samples had moderate quality of life. Results of functional status showed that most patients (61.4%) were able to perform normal activity and functional status scores range between 20 to 100.There was significant and inversely statistical differences between fatigue and quality of life. (r = - 0/69, p <0/000). Functional status was significantly and inversely correlated with fatigue (r = - 0 / 58, p <0/000). Conclusion: cancer patients experienced moderate fatigue. Considering relationship between fatigue with quality of life and functional status, it's necessary to be considered action to reduction of fatigue and therefore improve of quality of life and functional status of cancer patients. Keywords: Health-related quality of life, fatigue, cancer, cancer, functional status REF